2022
DOI: 10.7150/jca.65400
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Cigarette Smoking on the Tumor Immune Microenvironment in Esophageal Squamous Cell Carcinoma

Abstract: Objective: Cigarette smoking is a carcinogenic factor for esophageal cancer and evidence also indicates its effects on tumor microenvironment in patients with esophageal squamous cell carcinoma (ESCC). Materials and Methods:In our study, we demonstrated nine immune infiltrating cells and markers in non-smokers and smokers of 189 non-drinking ESCC patients with multiplex fluorescent immunohistochemistry (mflHC) staining and multispectral imaging. The impacts of cigarette smoking on tumor microenvironment and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Cancer is a disease mainly caused by abnormal signaling pathways. Smoking and drinking can cause changes in the microenvironment of the human body [ 34 , 35 ]. In our study, adverse factors such as JAG1, Wnt, ECM, EGF and IGF1 produced by the human microenvironment ultimately lead to cellular dysfunctions.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer is a disease mainly caused by abnormal signaling pathways. Smoking and drinking can cause changes in the microenvironment of the human body [ 34 , 35 ]. In our study, adverse factors such as JAG1, Wnt, ECM, EGF and IGF1 produced by the human microenvironment ultimately lead to cellular dysfunctions.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, numerous scientific studies have shown that smoking cigarettes can significantly reduce the blood flow necessary for wounds to heal properly. 45 Finally, in another study carried out in Spain, using a propensity score matching analysis, the authors found no impact of smoking on survival of melanoma patients and that it should not influence treatment decisions. 46 With all these data, and given that our data show an association between smoking and mortality, we hypothesize that the smoking patients included in our study could present more aggressive melanomas.…”
Section: Discussionmentioning
confidence: 97%
“…Smoking can also be a detriment to healing from skin cancer surgery. In fact, numerous scientific studies have shown that smoking cigarettes can significantly reduce the blood flow necessary for wounds to heal properly 45 . Finally, in another study carried out in Spain, using a propensity score matching analysis, the authors found no impact of smoking on survival of melanoma patients and that it should not influence treatment decisions 46 .…”
Section: Discussionmentioning
confidence: 98%
“…In never smokers and oncogene-addicted tumors, the number of somatic TMBs is lower, and the PD-L1 upregulation, which is often present, has a different biological role [ 17 ]. The tumor microenvironment is mostly poorly inflamed and results in a cold immune phenotype, which can explain the modest activity of IO [ 18 ].…”
Section: Io In Never-smoker And/or Oncogene-addicted Nsclc Patientsmentioning
confidence: 99%